Implementation of service marketing strategies to improve donor experience and loyalty on the Infak.id platform - Nugraha, Rendi Septiyan (Global Academy of Business Studies, 2025)
Purpose: This study aimed to explore the underlying factors contributing to the relatively low number of repeat donors on the Infak.id platform, which has constrained growth in donation activities. It also seeks to map possible business improvisations and propose service marketing strategies to address these challenges and enhance the platform’s long-term performance. Research Methodology: A quantitative approach was adopted, utilizing tools such as Canva Persona, Customer Journey Mapping, and Service Marketing Design. These methods were employed to investigate donor behavior, analyze user experiences across various touchpoints, and identify service gaps that may hinder repeat donations. Data were collected through surveys and processed using descriptive statistical techniques to highlight key patterns and donor pain points. Results: The findings indicate that donors encounter less engaging experiences, particularly in the final stages of interaction with the platform. Although overall satisfaction rates remain high, limited post-donation engagement significantly reduces intentions to donate again. This suggests the need for improvements not only in the donation process but also in maintaining meaningful relationships after transactions. Conclusions: Enhancing donor experience through optimizing business process flows, introducing features such as donation reminders and auto-debit systems, and improving transparency in fund reporting is essential to strengthen engagement and loyalty. These strategies are expected to increase repeat donations and improve financial sustainability. Limitations: This study focused on a single platform and relied mainly on quantitative data, potentially overlooking deeper qualitative donor motivations. Contribution: This study provides a practical framework for applying service marketing strategies to digital philanthropic platforms, offering insights to improve user experience, satisfaction, and loyalty.